2021
DOI: 10.3390/bios11010019
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hypoxanthine from Inosine and Unusual Hydrolysis of Immunosuppressive Drug Azathioprine through the Formation of a Diruthenium(III) System

Abstract: Hypoxanthine (hpx) is an important molecule for both biochemistry research and biomedical applications. It is involved in several biological processes associated to energy and purine metabolism and has been proposed as a biomarker for a variety of disease states. Consequently, the discovery and development of systems suitable for the detection of hypoxanthine is pretty appealing in this research field. Thus, we have obtained a stable diruthenium (III) compound in its dehydrated and hydrated forms with formula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…As a continuation of our interest in investigating biomolecule-based complexes [ 15 , 16 , 17 , 18 , 19 , 20 ], herein we report the synthesis and characterization of a new gadolinium(III) complex of formula [Gd(thy) 2 (H 2 O) 6 ](ClO 4 ) 3 ·2H 2 O ( 1 ) [thy = thymine], which exhibits a linearly disposed thymine-Gd III -thymine structure ( Figure 1 and Figure S1 ). 1 displays the first reported crystal structure based on gadolinium and thymine and is a suitable candidate for contrast-enhanced magnetic resonance (MR) imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a continuation of our interest in investigating biomolecule-based complexes [ 15 , 16 , 17 , 18 , 19 , 20 ], herein we report the synthesis and characterization of a new gadolinium(III) complex of formula [Gd(thy) 2 (H 2 O) 6 ](ClO 4 ) 3 ·2H 2 O ( 1 ) [thy = thymine], which exhibits a linearly disposed thymine-Gd III -thymine structure ( Figure 1 and Figure S1 ). 1 displays the first reported crystal structure based on gadolinium and thymine and is a suitable candidate for contrast-enhanced magnetic resonance (MR) imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…These diluted serum samples are transferred to an electrochemical cell containing 10 mL of PBS. Then, known concentrations of AP (5,10,15, and 20 M) were spiked into the electrochemical cell. The recovery results for all of the reduction peak currents determined by DPV (Figure 8A) are summarized in Table 2.…”
Section: Real-time Detection Of Apmentioning
confidence: 99%
“…Currently, the increase in azathioprine (AP; IUPAC 6-[(1-methyl-4-nitro-1 H -imidazol-5-yl)­thio]-9 H -purine) and its detection study are seen as very vital research prospects from the perspective of scientific, chemical, and biological development. AP is a purine synthesis inhibitor that is also used as an immunosuppressive drug along with other medicines to deter organ transplantation rejection . AP is also utilized to treat autoimmune diseases like rheumatoid arthritis . AP is a precursor of a drug that is transformed in the human body into its mercaptopurine and acts by reducing the impact of certain cells in the body’s immune system .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with xanthine, hypoxanthine may provide a sensitive indicator for physiological diseases, and therefore has been proposed as a biomarker for a diverse range of disease states, including Alzheimer's disease, multiple sclerosis, and colorectal cancer [4]. It is also found that local secretion of hypoxanthine by human adipose tissues was increased under hypoxia [5].…”
Section: Introduction mentioning
confidence: 99%